The interpretation of Use of Adjuvant Bisphosphonates and Other Bone-Modifying Agents in Breast Cancer: ASCO-OH (CCO) Guideline Update - LU Yujie, ZHU Siji (Waike lilun yu shijian)
Bone-modifying agents (BMAs), including bisphosphonate (BP) and denosumab, can reduce bone-related events caused by breast cancer bone metastasis. “Use of Adjuvant Bisphosphonates and Other Bone-Modifying Agents in Breast Cancer: ASCO-OH (CCO) Guideline Update” was published in Journal of Clinical Oncology in January 2022. The new “2022 version Guideline” suggested that the use of BP should be discussed for all postmenopausal patients with early breast cancer who are indicated for adjuvant therapy. Recommended drugs included zoledronate, clodronate, and ibandronate, and the recommended duration of BP was 2-3 years. Owing to the inconsistent results of the ABCSG-18 and D-CARE trials and the lack of data directly comparing denosumab with BP in early breast cancer, the use of denosumab in adjuvant therapy was not recommended. In conclusion, the role of BP in the adjuvant treatment of early breast cancer has been further affirmed, while the value of denosumab remains unclear.